Is text static or is it procedural? - Chernyavskaya, V. Ye. (Cognition, Communication, Discourse, 2018)
This article solves the problems of text by enlarging the object of analysis and considers the text in the new coordinate system as coexistent with discourse. Activity based nature of the text defines its processuality as its  internal characteristic. The text and text categories are "soft" by nature, they are determined by the joint activity of the communicants’ consciousness.